Rapid evolution of knockdown resistance haplotypes in response to pyrethroid selection in Aedes aegypti. (9th July 2021) - Baltzegar, Jennifer; Vella, Michael; Gunning, Christian; Vasquez, Gissella; Astete, Helvio; Stell, Fred; Fisher, Michael; Scott, Thomas W.; Lenhart, Audrey; Lloyd, Alun L.; Morrison, Amy; Gould, Fred
Abstract: This study describes the evolution of knockdown resistance (kdr) haplotypes in Aedes aegypti in response to pyrethroid insecticide use over the course of 18 years in Iquitos, Peru. Based on the duration and intensiveness of sampling (~10, 000 samples), this is the most thorough study of kdr population genetics in Ae .  aegypti to date within a city. We provide evidence for the direct connection between programmatic citywide pyrethroid spraying and the increase in frequency of specific kdr haplotypes by identifying two evolutionary events in the population. The relatively high selection coefficients, even under infrequent insecticide pressure, emphasize how quickly Ae .  aegypti populations can evolve. In our examination of the literature on mosquitoes and other insect pests, we could find no cases where a pest evolved so quickly to so few exposures to low or nonresidual insecticide applications. The observed rapid increase in frequency of resistance alleles might have been aided by the incomplete dominance of resistance‐conferring alleles over corresponding susceptibility alleles. In addition to dramatic temporal shifts, spatial suppression experiments reveal that genetic heterogeneity existed not only at the citywide scale, but also on a very fine scale within the city.